A feather-like structure of β-Al2TiO5 film prepared by laser chemical vapor deposition. Issue 7 (July 2015) - Ito, Akihiko; Nishigaki, Shotaro; Goto, Takashi
Abstract β-Al2TiO5 film with a feather-like structure was prepared by laser chemical vapor deposition. The β-Al2TiO5 film consisted of columnar grains. Oriented microcolumns grew on the side of the columnar grains, forming a feather-like structure. Saw-like nanostructures were developed on the microcolumns. The microstructural evolutions of columns and nanostructures in the feather-like structure are associated with the pseudobrookite β-Al2TiO5 crystal structure.